2020
DOI: 10.12659/msm.924092
|View full text |Cite
|
Sign up to set email alerts
|

Potential Molecular Mechanisms and Drugs for Aconitine-Induced Cardiotoxicity in Zebrafish through RNA Sequencing and Bioinformatics Analysis

Abstract: Background:Accumulating evidence suggests that cardiotoxicity is one of the main manifestations of aconitine (AC) poisoning. However, the molecular mechanism of AC-induced cardiotoxicity remains unclear, there is little direct evidence for therapeutic targets and drugs of AC-induced cardiotoxicity. Material/Methods:Zebrafish were exposed to AC to evaluate cardiotoxicity by calculating the heart rates and observing the changes of cardiac and vascular structure. RNA-seq (RNA sequencing) and bioinformatics analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Furthermore, an increase in coiling frequency, also a sign of embryotoxicity, has been reported recently. Wang et al found that AC-induced cardiotoxicity in zebrafish predominantly included arrhythmias, extended sinus venous and bulbus arteriosus (SV-BA) distance, and larger pericardial edema aera ( Wang et al, 2020 ). So far only one report had been published and showed that AC had direct embryotoxic effects during the rat organogenetic period ( Xiao et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an increase in coiling frequency, also a sign of embryotoxicity, has been reported recently. Wang et al found that AC-induced cardiotoxicity in zebrafish predominantly included arrhythmias, extended sinus venous and bulbus arteriosus (SV-BA) distance, and larger pericardial edema aera ( Wang et al, 2020 ). So far only one report had been published and showed that AC had direct embryotoxic effects during the rat organogenetic period ( Xiao et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…The heart rate of SD rats was seen in clear rising in one study ( Zhang et al, 2012 ). Conformably, aconitine-evoked a remarkable rise in heart rate was also demonstrated in zebrafish embryo models compared with the control group in a dose-response relationship ( Fang et al, 2012 ; Cui et al, 2018 ; Wang M. et al, 2020 ; Xia et al, 2021 ; Ye et al, 2021 ). A meta-analysis of two studies ( Fang et al, 2012 ; Wang S. et al, 2020 ) for the increased heart rate in zebrafish embryos [ n = 56, SMD = 2.42, 95% CI (1.56 to 3.27), p < 0.00001; heterogeneity: χ 2 = 30.32, df = 1 ( p < 0.00001), I 2 = 97%] ( Figure 3E ).…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, 21 studies were deleted because the outcome measurement was not of interest. Ultimately, 32 eligible articles ( Liang et al, 1991 ; Meng, 2006 ; Fu, 2007 ; Liu, 2007 ; Wang, 2007 ; Wang et al, 2007 ; Zhang, 2007 ; Xu, 2008 ; Liu, 2009 ; Deng, 2010 ; Fang et al, 2012 ; Zhang et al, 2012 ; Wang, 2013 ; Zhou et al, 2013 ; Sun et al, 2014 ; Yu, 2015 ; Cui et al, 2018 ; Gao, 2018 ; Gao et al, 2018 ; Hu et al, 2018 ; Li et al, 2018 ; Zhang et al, 2018 ; Liu et al, 2019 ; Wang M. et al, 2020 ; Li et al, 2020 ; Peng et al, 2020 ; Zhang et al, 2020 ; Zhou et al, 2020 ; Xia et al, 2021 ; Yang et al, 2021 ; Ye et al, 2021 ; Wang S. et al, 2022 ) were identified for further evaluation, data extraction, and analysis ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations